PENGARUH MANAJEMEN LABA DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONNSIBILITY SEBAGAI VARIABEL INTERVENING (Studi pada perusahaan manufaktur ya - Sumarni (AKT 16 UMY 066, 2016)
This study is aimed to prove the impact of management profit institutional ownership toward the value of the company by inspecting corporate social responsibility as variable intervening. Manufacturing companies which are registered in Bursa Efek Indonesian (BEI) 0n year 2011-2014 become object of the study. The technique of collecting data is done by searching annual report’s companies which have chosen to be sample of pojok BEI at University Muhammadiyah of Yogyakarta. The researcher use regress multiple linier to be an instrument analysis. Based on researcher’s analysis, the result showed that earnings management has positive impact and sifnificance toward value of the company by inspecting corporate social responsibility as variable intervening. Institutional ownership also has positive impact an significanne toward value of the company by inspecting corporate social responsibility as variable intervening. Key words: Earnings management, Institutional Ownership, The Value of company, and Corporate Social responsibility disclousure.